EVALUATING THE FUTURE PROSEPECT OF INDOFOOD CONSUMER BRANDED PRODUCT (ICBP) STOCK AMIDST PANDEMIC COVID-19 - Mawaridz, Farhan
Food and beverage industry in Indonesia is predicted to grow 77.8 percent in the next five years with total food and beverage sales reaching USD 3.535 trillion by 2024. PT Indofood CBP Sukses Makmur Tbk (ICBP), one of the leading consumer goods companies in food sector and beverages in Indonesia based on historical stock price data from 2016 to August 2021 experienced a minus growth of -5% but the company's average net income growth was positive at 16.75%. As a result of the COVID-19 pandemic, its share price since January 2021, which has been at a price of Rp. 9,758, companies also has decreased and has a volatile trend until August 2021 at a price of Rp. 8,150 then experienced a fluctuating trend in net income in year 2020. Based on these problems, the main purpose of this thesis is to find the intrinsic value of PT. Indofood CBP Sukses Makmur Tbk; valuation will be carried out based on a framework starting from identifying the external and internal conditions of PT. Indofood CBP Sukses Makmur Tbk, then SWOT analysis, porter five forces analysis and risk analysis. The results of the internal analysis show that financial performance in the industry and in general is better than last year's performance. For valuation, absolute valuation and relative valuation methods will be used to find the fair price of ICBP. The absolute valuation method used is the discounted cash flow (DCF) model, for relative valuation the price-to-earnings ratio (PER) and enterprise value/earnings before interest, taxes and depreciation (EV/EBITDA) are used. After that, a sensitivity analysis will be carried out on the fair value of ICBP shares. The valuation result of the DCF method is IDR 10,100 per share (23.03 percent above the market price of IDR 8,150). Relative valuation gives different results than DCF; PER analysis produces a price of Rp. 8,250 per share (1.23 percent above the market price) while the EV/EBITDA calculation result is Rp. 12,752.